2019
DOI: 10.1016/j.ebiom.2019.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin synthase 1 enhances BCR signaling to promote lupus-like autoimmune response

Abstract: Background Sphingomyelin synthase 1 (SMS1) has been reported to participate in hepatitis and atherosclerosis. However, its role in autoimmune response is not clear. This study investigates the possible involvement of SMS1 in B-cell activation and lupus-like autoimmunity. Methods SMS1 knockout lupus-like animal model and SLE patient samples were utilized. B-cell activation and associated signal transduction were detected by flow cytometry, confocal analysis and western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…A recent study showed that SMS1 deficiency suppressed B-cell activation and lupus-like autoimmunity such as systemic lupus erythematosus (SLE). 115 In an in vitro culture system of B cells, IgM-mediated activation and differentiation into plasma cells were suppressed in SMS1 deficient cells. Interestingly, supplementation of SM in the culture media recovered both activation and differentiation in SMS1-KO B cells.…”
Section: Phenotypes Of Smss-ko Mice In Disease Modelsmentioning
confidence: 99%
“…A recent study showed that SMS1 deficiency suppressed B-cell activation and lupus-like autoimmunity such as systemic lupus erythematosus (SLE). 115 In an in vitro culture system of B cells, IgM-mediated activation and differentiation into plasma cells were suppressed in SMS1 deficient cells. Interestingly, supplementation of SM in the culture media recovered both activation and differentiation in SMS1-KO B cells.…”
Section: Phenotypes Of Smss-ko Mice In Disease Modelsmentioning
confidence: 99%
“…In addition, although 2OHOA can activate both SMS1 and SMS2, we believe that its therapeutic effect on lupus is achieved via activation of SMS2. This is because a recent study showed that systemic SMS1 deficiency attenuated the pathogenesis of lupus in pristane and bm12 models (Wang et al, 2019), in which innate immune responses play a central regulatory role in pathogenesis (Han et al, 2017;Shi et al, 2014;Zhao et al, 2007). Therefore, the evidence points to SMS2 as the primary target of 2OHOA in autoreactive dsDNA-specific GC B cells, in keeping with the highly upregulated expression of SMS2, but not SMS1, in these cells (Figure 4).…”
Section: Discussionmentioning
confidence: 70%
“…47 Moreover, T-and B-cell activations through their receptors were prevented by SM depletion of DRMs in SMS1-KO mice, resulting in SM-deficient amelioration of hepatitis or systemic lupus erythematosus, but not in SMS2-KO mice. 19,48 Furthermore, JEV can achieve infection by attaching to target cell membranes through SMS1-generated SM. 23 Consequently, SMS1-KO mice are protected from JEV infection and JEV-mediated encephalitis.…”
Section: Discussionmentioning
confidence: 99%